A Comparative Study of LIS Educational Frameworks in Australia, New Zealand, United States and Canada. - White, Hollie; Gibbons, Leisa (Association for Library and Information Science Education, 2019)
As Library and Information Science (LIS) educators, we teach our students about the changing and evolving role of the information professional in the twenty-first century. For many educators around the world, accreditation of LIS programs also shapes and legitimizes curriculum. This comparative study of the United States, Canada, Australia, and New Zealand seeks to identify similarities and differences in accreditation frameworks. This research shows that similarities and differences exist in programs, course designs, delivery methods, accreditation models, program specializations, and engagement with information science as a discipline. In conclusion we ask five critical questions about Australian LIS education and propose three areas for future research, including evaluating the purpose of accreditation.